Deterioration of the fixation segment’s stress distribution and the strength reduction of screw holding position together cause screw loosening in ALSR fixed OLIF patients with poor BMD - Li, Jing-Chi; Yang, Zhi-Qiang; Xie, Tian-Hang; Song, Zhe-Tao; Song, Yue-Ming; Zeng, Jian-Cheng (Frontiers in Bioengineering and Biotechnology, 2022)
The vertebral body's Hounsfield unit (HU) value can credibly reflect patients' bone mineral density (BMD). Given that poor bone-screw integration initially triggers screw loosening and regional differences in BMD and strength in the vertebral body exist, HU in screw holding planes should better predict screw loosening. According to the stress shielding effect, the load transmission pattern changes in the fixation segment with BMD reduction should be related to screw loosening, but this has not been identified. We retrospectively collected the radiographic and demographic data of 56 patients treated by single-level oblique lumbar interbody fusion (OLIF) with anterior lateral single rod (ALSR) screw fixation. BMD was identified by measuring HU values in vertebral bodies and screw holding planes. Regression analyses identified independent risk factors for cranial and caudal screw loosening separately. Meanwhile, OLIF with ALSR fixation was numerically simulated; the elastic modulus of bony structures was adjusted to simulate different grades of BMD reduction. Load transmission pattern changes were judged by computing stress distributions in screws, bone-screw interfaces, and cancellous bones in the fixation segment. The results showed that HU reduction in vertebral bodies and screw holding planes were independent risk factors for screw loosening. The predictive performance of screw holding plane HU is better than the mean HU of vertebral bodies. Cranial screws suffer a higher risk of screw loosening, but HU was not significantly different between cranial and caudal sides. The poor BMD led to stress concentrations on both the screw and bone-screw interfaces. Biomechanical deterioration was more severe in the cranial screws than in the caudal screws. Additionally, lower stress can also be observed in fixation segments' cancellous bone. Therefore, a higher proportion of ALSR load transmission triggers stress concentration on the screw and bone-screw interfaces in patients with poor BMD. This, together with decreased bony strength in the screw holding position, contributes to screw loosening in osteoporotic patients biomechanically. The trajectory optimization of ALSR screws based on preoperative HU measurement and regular anti-osteoporosis therapy may effectively reduce the risk of screw loosening.